Las Indias de aquí: misiones interiores en Castilla, siglos XVI-XVII - Arranz Roa, Íñigo (Estudios eclesiásticos, 2007)
This article first explains the nature of the Jesuits’ global civilizing mission as a key feature of their institutional character. Since 1990 the concept of «Indies in the old country» or Internal Missions has been one of the leading interpretative categories in the historiography of European Early Modern Catholicism. The great number of records, attests a strong activity in the former Jesuit stronghold of Castile from the second half of 16th century. The action undertaken by Jesuits in Castile demonstrates the role played by internal missions in regard to the articulation of their society, in accordance with the patterns of behaviour and the models of political organization of this period.